Evaluation of Three Rapid Methods for Detection of Methicillin Resistance in Staphylococcus aureus - Louie, L. (American Society for Microbiology, 2000)
The probe-based Velogene Rapid MRSA Identification Assay (ID Biomedical Corp., Vancouver, British Columbia, Canada) and the latex agglutination MRSA-Screen (Denka Seiken Co., Tokyo, Japan) were evaluated for their ability to identify methicillin-resistant Staphylococcus aureus (MRSA) and to distinguish strains of MRSA from borderline oxacillin-resistant S. aureus (BORSA; mecA-negative, oxacillin MICs of 2 to 8 μg/ml). The Velogene is a 90-min assay using a chimeric probe to detect the mecA gene. MRSA-Screen is a 15-min latex agglutination test with penicillin-binding protein 2a antibody-sensitized latex particles. We compared these assays with the BBL Crystal MRSA ID System (Becton Dickinson, Cockeysville, Md.) and with PCR for mecA gene detection. A total of 397 clinical isolates of S. aureus were tested, consisting of 164 methicillin-susceptible strains, 197 MRSA strains, and 37 BORSA strains. All assays performed well for the identification of MRSA with sensitivities and specificities for Velogene, MRSA-Screen, and BBL Crystal MRSA ID of 98.5 and 100%, 98.5 and 100%, and 98.5 and 98%, respectively. Three MRSA strains were not correctly identified by each of the Velogene and MRSA-Screen assays, but repeat testing with a larger inoculum resolved the discrepancies. The BBL Crystal MRSA ID test misclassified four BORSA strains as MRSA. Both the Velogene and the MRSA-Screen assays are easy to perform, can accurately differentiate BORSA isolates from MRSA isolates, and provide a rapid alternative for the detection of methicillin resistance in S. aureus in clinical laboratories, especially when mecA PCR gene detection is unavailable.